Biomechanical Responses and Injury Characteristics of Knee Joints under Longitudinal Impacts of Different Velocities. (5th August 2018) - Xiong, Yan; Zhao, Xueliang; Xiang, Hongyi; Wang, Yunjiao; Liao, Zhikang; Zhu, Xiyan; Zhao, Hui
Abstract : Background and Objective . Knee joint collision injuries occur frequently in military and civilian scenarios, but there are few studies assessing longitudinal impacts on knee joints. In this study, the mechanical responses and damage characteristics of knee longitudinal collisions were investigated by finite element analysis and human knee impact tests. Materials and methods . Based on a biocollision test plateau, longitudinal impact experiments were performed on 4 human knee joints (2 in the left knee and 2 in the right knee) to measure the impact force and stress response of the bone. And then a finite element model of knee joint was established from the Chinese Visible Human (CVH), with which longitudinal impacts to the knee joint were simulated, in which the stress response was determined. The injury response of the knee joint-sustained longitudinal impacts was analyzed from both the experimental model and finite element analysis. Results. The impact experiments and finite element simulation found that low-speed impact mainly led to medial injuries and high-speed impact led to both medial and lateral injuries. In the knee joint impact experiment, the peak flexion angles were 13.8° ± 1.2, 30.2° ± 5.1, and 92.9° ± 5.45 and the angular velocities were 344.2 ± 30.8 rad/s, 1510.8 ± 252.5 rad/s, and 9290 ± 545 rad/s at impact velocities 2.5 km/h, 5 km/h, and 8 km/h, respectively. When the impact velocity was 8 km/h, 1 knee had a femoral condylar fracture and 3 knees had medial tibial plateau fractures or collapse fractures. The finite element simulation of knee joints found that medial cortical bone stress appeared earlier than the lateral peak and that the medial bone stress concentration was more obvious when the knee was longitudinally impacted. Conclusion . Both the experiment and FE model confirmed that the biomechanical characteristics of the injured femur and medial tibia are likely to be damaged in a longitudinal impact, which is of great significance for the prevention and treatment of longitudinal impact injuries of the knee joint.